2016
DOI: 10.1093/mnras/stw3011
|View full text |Cite
|
Sign up to set email alerts
|

(Star)bursts of FIRE: observational signatures of bursty star formation in galaxies

Abstract: Galaxy formation models are now able to reproduce observed relations such as the relation between galaxies' star formation rates (SFRs) and stellar masses (M * ) and the stellar masshalo mass relation. We demonstrate that comparisons of the short-timescale variability in galaxy SFRs with observational data provide an additional useful constraint on the physics of galaxy formation feedback. We apply SFR indicators with different sensitivity timescales to galaxies from the Feedback in Realistic Environments (FIR… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

33
258
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 248 publications
(300 citation statements)
references
References 115 publications
(145 reference statements)
33
258
4
Order By: Relevance
“…Moreover, on average, the below-MS galaxies tend to have lower SFRs at all radii than above-MS galaxies (but this is not true of the individual profiles) because these galaxies have, on average, lower gas surface densities (Figure 3) than the above-MS galaxies (owing to stochasticity in gas accretion from both the intergalactic medium and galactic fountains and/or recent strong outflows driven by stellar feedback; Muratov et al 2015;Anglés-Alcázar et al 2017;. However, in the simulations, these differences are stochastic rather than long-lived, as is evident from the bottom panel of Figure 4, and the FIRE galaxies can cross the MS multiple times within 100 Myr (Figure 2; see also Sparre et al 2017). Note, however, that the galaxies considered here are of relatively "low" stellar mass (   M 10 10  M ), and more massive simulated galaxies tend to exhibit less bursty star formation and smoother mass, metallicity, and SFR profiles, especially at low redshift (Ma et al 2017;Sparre et al 2017).…”
Section: Summary and Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…Moreover, on average, the below-MS galaxies tend to have lower SFRs at all radii than above-MS galaxies (but this is not true of the individual profiles) because these galaxies have, on average, lower gas surface densities (Figure 3) than the above-MS galaxies (owing to stochasticity in gas accretion from both the intergalactic medium and galactic fountains and/or recent strong outflows driven by stellar feedback; Muratov et al 2015;Anglés-Alcázar et al 2017;. However, in the simulations, these differences are stochastic rather than long-lived, as is evident from the bottom panel of Figure 4, and the FIRE galaxies can cross the MS multiple times within 100 Myr (Figure 2; see also Sparre et al 2017). Note, however, that the galaxies considered here are of relatively "low" stellar mass (   M 10 10  M ), and more massive simulated galaxies tend to exhibit less bursty star formation and smoother mass, metallicity, and SFR profiles, especially at low redshift (Ma et al 2017;Sparre et al 2017).…”
Section: Summary and Discussionmentioning
confidence: 90%
“…The observed MS (Whitaker et al 2014) and scatter (Speagle et al 2014) in two redshift bins intersecting this interval are shown. In this redshift and mass range, the individual simulated galaxies experience significant (sometimes an order of magnitude or more), rapid (timescales100 Myr) SFR variations (see Sparre et al 2017 for a detailed study) and clearly do not evolve parallel to the MS.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…How SFDGs assemble their stellar mass remains one of the unanswered questions surrounding these galaxies. Differently from high-mass (M * > 10 9 M ) galaxies, which show a continuous rate of star formation (SF), the most common scenario for dwarf galaxies is the cyclic bursty mode, as pointed out by theoretical models (e.g., Hopkins et al 2014;Sparre et al 2017) and observations (Guo et al 2016b). Intense SF episodes produce stellar feedback through strong winds and supernova, which heat and expel the surrounding gas in outflows, eventually resulting in a temporary quenching of SF on timescales of tens of Myr (e.g., Olmo-Garcia et al 2017;Pelupessy et al 2004).…”
Section: Introductionmentioning
confidence: 99%